2018
DOI: 10.1253/circj.cj-17-0419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive and Standard Pitavastatin Treatment With or Without Eicosapentaenoic Acid on Progression of Coronary Artery Calcification Over 12 Months ― Prospective Multicenter Study ―

Abstract: studies showing significant regression of CAC and contemporaneous data showing opposite results. 3-6 Several randomized controlled clinical trials have failed to show attenuation of progression of CAC despite a significant lowering of low-density lipoprotein cholesterol (LDL-C) by atorvastatin or pravastatin. 7-11 Pitavastatin has been reported to substantially reduce LDL-C, as have other statins. 12 A previous study showed a significant increase in T he prevalence of coronary artery calcification (CAC) is age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Early initiation of treatment with EPA combined with statin after successful primary PCI reduced CVD events after ACS 68) . On the contrary, standard treatment with EPA did not reduce the progression of coronary artery calcification compared with standard pitavastatin treatment 69) .…”
Section: Vascular Effect and Anti-arteriosclerotic Effect Of Omega-3 mentioning
confidence: 71%
“…Early initiation of treatment with EPA combined with statin after successful primary PCI reduced CVD events after ACS 68) . On the contrary, standard treatment with EPA did not reduce the progression of coronary artery calcification compared with standard pitavastatin treatment 69) .…”
Section: Vascular Effect and Anti-arteriosclerotic Effect Of Omega-3 mentioning
confidence: 71%
“…Blood levels of n-3 polyunsaturated fatty acid and omega-3 index and the percentages of EPA and docosahexaenoic acid (DHA) in total fatty acids present in the erythrocyte membrane have been shown to be inversely associated with coronary artery calcification in some observational studies [25,27,28]. On the other hand, we reported that 1.8 g/day EPA does not attenuate progression of coronary artery calcification evaluated by CT in pitavastatin-treated patients with hypercholesterolemia who were asymptomatic for cardiovascular disease during a period of 12 months [26]. Evaluation using optical coherence tomography and intravascular ultrasound showed that the addition of 1.8 g/day EPA to statin therapy does not change the calcified plaque volume, even though it does stabilize and reduce plaques of human coronary arteries [123][124][125].…”
Section: Effects Of Epa On Arterial Calcification In Clinical Studiesmentioning
confidence: 81%
“…However, the effect of EPA on arterial calcification in a clinical situation is not established. While the blood level of omega-3 fatty acid was shown to be inversely associated with coronary artery calcification in some observational studies, pitavastatin plus EPA did not reduce the progression of coronary artery calcification compared with the effect of pitavastatin alone in patients with hypercholesterolemia [25][26][27][28]. Since there is a discrepancy in the effect of EPA among the results of clinical observational, clinical interventional and experimental studies, we reviewed the effect of EPA on arterial calcification.…”
Section: Introductionmentioning
confidence: 99%
“…The current study was a pre-specified sub-analysis of the PEACH study [12]. Eligible patients were adults ( > 20 years old) with an Agatston score of 1 to 999, with hypercholesterolemia (LDL cholesterol ≥ 140 mg/dL at screening or taking a statin), and no history of CVD.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported the results of a prospective multicenter study (Effect of pitavastatin and EPA on coronary artery calcification detected by computed tomography: PEACH study) that examined the effects of intensive and standard pitavastatin treatment with or without eicosapentaenoic acid (EPA) on the annual progression of CAC [12]. In that study, we found that the overall CAC progression rate over 1 year was 40% and that the CAC progression in each patient group was not affected by the allocated treatments.…”
mentioning
confidence: 99%